Pterotylenchus cecidogenus n. gen., n. sp., a new stem-gall nematode parasitizing Desmodium ovalifolium in Colombia - Siddiqi, MR; Lenné, Jillian M. (1984)
Pterotylenchus cecidogenus n. gen., n. sp. from stem-galls of Desmodium ovalifolium Wall. in Colombia is described and illustrated. The new genus belongs to Anguinidae and is related to Orrina Brzeski, 1980 but is unique in having large vulval flaps. P. cecidogenus has females with body 0.59-0.8 mm long, stylet 9-11 ?m long, no median oesophageal bulb, a crustaformeria of 32-36 cells, a short post-vulval uterine sac, and a conical pointed tail.